2021
DOI: 10.37506/mlu.v21i1.2424
|View full text |Cite
|
Sign up to set email alerts
|

Common Warts Treatment by Intralesional (60,000 Versus 120,000) IU of Vitamin D3, Comparative Study

Abstract: Background:Wart is common disease cause by infection with HPV, there are many modalities for treatment most of them resolve wart with many side effects as scars and recurrence.Objective: To identify the significant difference between two doses of intralesional vitamin D3 (60,000 vs 120,000) iu injection in treatment of warts.Patients and Method: A total of 47 patients were included in the study divided into two groups. Group A received intralesional 60,000 iu of vt.D3, and group B received intralesional 120,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Amin et al compared cryotherapy with intralesional vitamin D3 (5 mg/ml) for warts on the hands and feet and showed similar efcacy for both modalities [10]. In another study, Ihsan Mahmoud and Ayyash used 60,000 and 120,000 IU of intralesional vitamin D3 for common warts and found both efective without any signifcant diference [11]. Additionally, Kumar and Brar demonstrated that 600,000 IU intralesional vitamin D3 was safe and efective for the treatment of palmoplantar warts [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amin et al compared cryotherapy with intralesional vitamin D3 (5 mg/ml) for warts on the hands and feet and showed similar efcacy for both modalities [10]. In another study, Ihsan Mahmoud and Ayyash used 60,000 and 120,000 IU of intralesional vitamin D3 for common warts and found both efective without any signifcant diference [11]. Additionally, Kumar and Brar demonstrated that 600,000 IU intralesional vitamin D3 was safe and efective for the treatment of palmoplantar warts [17].…”
Section: Discussionmentioning
confidence: 99%
“…Tis leads to the modulation of innate immunity [7]. Intralesional vitamin D has been shown to be safe and efective for the treatment of warts [8][9][10][11]. Very few studies have also demonstrated the efcacy of topical vitamin D derivatives in this regard, including a case report and a study on 17 patients [12,13].…”
Section: Introductionmentioning
confidence: 99%